1987
DOI: 10.1037/0021-843x.96.3.199
|View full text |Cite
|
Sign up to set email alerts
|

Construct accessibility and clinical depression: A longitudinal investigation.

Abstract: This document is copyrighted by the American Psychological Association or one of its allied publishers.This article is intended solely for the personal use of the individual user and is not to be disseminated broadly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
136
1
6

Year Published

1993
1993
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 259 publications
(159 citation statements)
references
References 43 publications
16
136
1
6
Order By: Relevance
“…This finding is inconsistent with previous studies that have utilised emotional versions of the Stroop colour-naming task to investigate attentional processing of emotional stimuli in patients with MD (e.g. Gotlib & Cane, 1987;Nunn, Mathews & Trower, 1997;Segal et al, 1995), as they reported interference from negative as opposed to positive stimuli. However, it should be noted that the observed difference in the present study failed to reach conventional significance and thus would require replication with a larger sample before any implications could be considered.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…This finding is inconsistent with previous studies that have utilised emotional versions of the Stroop colour-naming task to investigate attentional processing of emotional stimuli in patients with MD (e.g. Gotlib & Cane, 1987;Nunn, Mathews & Trower, 1997;Segal et al, 1995), as they reported interference from negative as opposed to positive stimuli. However, it should be noted that the observed difference in the present study failed to reach conventional significance and thus would require replication with a larger sample before any implications could be considered.…”
Section: Discussioncontrasting
confidence: 56%
“…For example, studies that have utilised emotional variants of the Stroop colour-naming task (e.g. Gotlib & Cane, 1987;Nunn, Mathews & Trower, 1997;Segal et al, 1995) have tended to demonstrate that depressed individuals are slower to colour-name depression-relevant words than positive or neutral words (usually interpreted as evidence of attention capture by the negative material). It has also been reported that patients with depression exhibit biased attentional processing of emotional faces (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…This finding is in line with the earlier studies that talk about interference as a vulnerability measure in MDD (Mathews & MacLeod, 2005). As stated by Gotlib and Cane (1987), depressed patients' performance in the SCWT is different, once while they are in a depressive episode and once again after their recovery from depression. The higher was the age level, the greater were the RTs and error rates.…”
Section: Discussionsupporting
confidence: 81%
“…As EC is in essence a measure of executive functioning, and as many experimental studies have shown that the lack of executive attention is found for various forms of psychopathology (Dobson & Dozois, 2004;Gotlib & Cane, 1987;Homack & Riccio, 2004;Mathews & Macleod, 1985;Sharma et al, 2001;Smith & Waterman, 2003), it is predicted that low EC should also be associated with them. In fact, empirical studies have shown that low EC is associated with both externalizing problems and internalizing problems (Eisenberg et al, 2001;Lemery et al, 2002;Oldehinkel et al, 2004).…”
mentioning
confidence: 99%